2023
DOI: 10.3389/fpls.2023.1067189
|View full text |Cite
|
Sign up to set email alerts
|

Spectral characterization and severity assessment of rice blast disease using univariate and multivariate models

Abstract: Rice is the staple food of more than half of the population of the world and India as well. One of the major constraints in rice production is frequent occurrence of pests and diseases and one of them is rice blast which often causes yield loss varying from 10 to 30%. Conventional approaches for disease assessment are time-consuming, expensive, and not real-time; alternately, sensor-based approach is rapid, non-invasive and can be scaled up in large areas with minimum time and effort.  In the present study, hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 85 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Liu and Ahmadi et al used an ANN approach to classify and identify rice glume blight and root rot of oil palm [92,93]. Mandal et al tested and validated the classification of rice blast severity using support vector machine regression (SVM), partial least squares (PLS), random forest (RF), and multivariate adaptive regression spline (MARS) methods; the results indicate that the RF model is optimal in both calibration and validation processes, with accuracies of 0.995 and 0.606, respectively [36]. Ma et al obtained canopy images of rice blast using drones and constructed neural networks (CNN), random forest (RF), and support vector regression (SVR) inversion algorithms based on spectra and vegetation indices.…”
Section: The Methods For Rice Diseases and Pests Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu and Ahmadi et al used an ANN approach to classify and identify rice glume blight and root rot of oil palm [92,93]. Mandal et al tested and validated the classification of rice blast severity using support vector machine regression (SVM), partial least squares (PLS), random forest (RF), and multivariate adaptive regression spline (MARS) methods; the results indicate that the RF model is optimal in both calibration and validation processes, with accuracies of 0.995 and 0.606, respectively [36]. Ma et al obtained canopy images of rice blast using drones and constructed neural networks (CNN), random forest (RF), and support vector regression (SVR) inversion algorithms based on spectra and vegetation indices.…”
Section: The Methods For Rice Diseases and Pests Monitoringmentioning
confidence: 99%
“…Das et al pointed out that spectral indices of normalized difference vegetation index (NDVI), enhanced vegetation index (EVI), normalized difference moisture index (NDMI), and SAVI can be used to predict the severity of rice leaf blast in large areas based on MODIS remote sensing images [35]. Mandal et al developed two hyperspectral indices of RBI (R1148, R1301) and NDBI (R1148, R1301) for identification of rice blast, with R2 of 0.85 and 0.86, respectively [36]. Using hyperspectral data from UAVs, Qin et al, of the Chinese Academy of Agricultural Sciences, showed that visible and near-infrared spectra could be used for monitoring rice blight and proposed a series of spectral indices for predicting the extent of rice pest development [37].…”
Section: Multispectral Technologymentioning
confidence: 99%
“…One of the most popular and extensively grown grains in the world, particularly in Asia and Africa, is rice. On the other hand, some illnesses cause biotic stress to rice, which leads to notable reductions in production and quality [1]. Blast is a harmful disease of rice that causes enormous damage every year in many areas where rice is cultivated.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major constraints in rice production is frequent occurrence of pests and diseases, and one of them is rice blast, which often causes yield losses ranging from 10 to 30%. [3]. The incidence of insects and diseases in rice fields varied depending on the season, weather, variety, etc.…”
Section: Introductionmentioning
confidence: 99%